The Role of Membranes in Modern Winemaking: From Clarification to Dealcoholization - Carolina E. Demaman Oro; Bruna M. Saorin Puton; Luciana D. Venquiaruto; Rogério Marcos Dallago; Giordana Demaman Arend; Marcus V. Tres (Membranes)
The utilization of membrane technologies in winemaking has revolutionized various stages of production, offering precise and efficient alternatives to traditional methods. Membranes, characterized by their selective permeability, play a pivotal role in enhancing wine quality across multiple processes. In clarification, microfiltration and ultrafiltration membranes, such as ceramic or polymeric membranes (e.g., polyethersulfone or PVDF), effectively remove suspended solids and colloids, resulting in a clearer wine without the need for chemical agents. During stabilization, membranes such as nanofiltration and reverse osmosis membranes, often made from polyamide composite materials, enable the selective removal of proteins, polysaccharides, and microorganisms, thereby improving the wine’s stability and extending its shelf life. Additionally, in dealcoholization, membranes like reverse osmosis and pervaporation membranes, typically constructed from polydimethylsiloxane (PDMS) or other specialized polymers, facilitate the selective removal of ethanol while preserving the wine’s flavor and aroma profile, addressing the increasing consumer demand for low-alcohol and alcohol-free wines. This article provides a comprehensive analysis of the advancements and applications of membrane technologies in winemaking.